Project-based or problem-based learning? Unveiling Islamic university students preferences and experiences in writing classes - Desti Angraini; Urip Sulistiyo; Eddy Haryanto; Aryawira Pratama (Studies in English Language and Education, 2025)
Project-Based Learning (PjBL) and Problem-Based Learning (PBL) have emerged as the leading teaching methods of this century. Thus, this study investigates the students preferences and experiences with PjBL and PBL in the development of writing skills at an Islamic university in Indonesia. Utilizing the qualitative analysis framework proposed by Miles and Huberman (1994), this research provides an in-depth examination of the students experiences, preferences, and the pedagogical efficacy of these two approaches. The data were collected through semi-structured interviews with the students who participated in writing courses that incorporated both PjBL and PBL strategies, allowing for a comprehensive comparison of their impacts on writing skills. The findings reveal that PjBL was particularly effective in enhancing the students writing abilities by nurturing sustained engagement, enabling thorough content exploration, and supporting iterative refinement through extended project work that integrates research, critical thinking, and feedback. In contrast, PBL proved valuable in promoting critical thinking and concise writing by utilizing structured problem-solving tasks. Overall, the study contributes to the discourse on effective writing instruction in higher education by suggesting that, while PjBL offered a more comprehensive framework for writing development, PBL served as a practical complementary method. The combined use of these strategies could, therefore, provide a balanced framework for enhancing the students academic writing proficiency.